PELATIHAN PEMBUATAN KONTEN PEMBELAJARAN DARING PADA SMK SWASTA GELORA JAYA NUSANTARA MEDAN - Rena Nainggolan; Roni Jhonson Simamora; Rasmulia Sembiring; Mendarissan Aritonang; Siti Normi; Junika Napitupulu; Melanthon Rumapea; Mufria J. Purba; Rijois I. E. Saragih (Universitas Methodist Indonesia, 2021)
The purpose of community service activities is to implement the Tri Dharma of Higher Education and to contribute ideas and transfer technology to teaching staff at SMK Gelora Jaya Nusantara Medan. This service activity was carried out for 2 days. The training materials are Video Recording and Video Editing. The topic given in this training is the creation of online learning content. The material given is the use of Filmora X software. This topic is very much needed to equip teachers in preparing and delivering subject matter during this covid-19 pandemic. This topic was deliberately chosen considering that currently, teachers have difficulty in delivering subject matter face to face.